ACCOUNTANTS' PROGRESSIVITY DEMANDS IN THE AGE OF DIGITAL ACCOUNTING - WA ASRIDA; RASNI HANIPA USEMAHU (CV KULTURA DIGITAL MEDIA, 2023)
The world is indeed moving fast and agile, especially in the perspective of technology and information. This agile movement of technology has the consequence of how various fields of life are required to be in line with the behavior of the technology. The purpose of this research is to find out how the accounting profession is facing the existence of digital accounting in this era of pampering by technology. This research method is qualitative with data collection methods, literature studies and literature studies. The results of this study indicate that the role of the accounting profession has moved on from the era before society 5.0. But this will not lead to the disappearance of the accounting profession in the future, because there are roles that are irreplaceable, namely roles based on feelings and feelings. All that is needed is a transformation towards technological literacy, analytical and critical thinking skills, communication fluency, and emotional management